Lean logistics the nuts and bolts of delivering materials and goods - Baudin, Michel (Productivity Press, 2004)
Lean Logistics: The Nuts and Bolts of Delivering Materials and Goods by Michel Baudin helps you determine whether you have the right supply to meet your customers' demands, as well as the ability to organize and deliver that supply. In this cutting edge work, Baudin addresses the physical infrastructure of lean logistics and the flow of information that composes its nervous system. He demonstrates the methods that will allow you to avoid shortages while maintaining low inventories, while showing you how to take advantage of the increased capacity and flexibility generated through lean manufacturing.